God becomes beautiful … in mathematics - Kessler, Volker (HTS teologiese studies, 2018)
This article is transdisciplinary in that it touches on the disciplines of both mathematics and theology. It is about the mysterious link between truth and beauty in mathematics. It uses the theological pattern laid by the practical theologian Bohren in his book, God’s Becoming Beautiful. Mathematics can be seen as science or art. I argue that in both cases, we could conclude that God becomes beautiful in mathematics. This leads to the observation that there is some spirituality in mathematics. This insight might also have practical implications for mathematics education in schools.